Method for Determining Non-Isomorphism of Graphs (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Among the numerous examples of application areas of algorithms for solving the problem of determining graph isomorphism, we note the problem of syntactic and structural pattern recognition, some problems of mathematical chemistry and chemoinformatics (study of the molecular structures of chemical compounds), problems related to the study of social networks (for example, linking several accounts of one user on Facebook).